PERAN KONSELING INDIVIDUAL DENGAN PENDEKATAN COGNITIVE BEHAVIOR THERAPY (CBT) UNTUK MENGATASI SOCIAL ANXIETY SISWA KELAS X SMA NEGERI COLOMADU TAHUN PELAJARAN 2025/2026 - Damayanti, Fitri; Hera Heru Sri Suryanti; Eko Adi Putro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fitri Damayanti. THE ROLE OF INDIVIDUAL COUNSELING USING COGNITIVE BEHAVIOR THERAPY (CBT) APPROACH TO OVERCOME SOCIAL ANXIETY IN CLASS X STUDENTS OF SMA NEGERI COLOMADU ACADEMIC YEAR 2025/2026. This study aims to determine the role of individual counseling with the CBT approach in overcoming social anxiety in class X students of SMA Negeri Colomadu. This research used Guidance and Counseling Action Research (PTBK) conducted in three cycles using the Kemmis and McTaggart model. The subject was a class X-2 student (SAF) identified as having high social anxiety. CBT techniques applied were thought monitoring, cognitive restructuring, behavioral experiment, and behavioral reinforcement. Observation results showed a decrease from 80% (pre-cycle) to 45% (cycle III), a total reduction of 35%. The social anxiety scale decreased by 31%, from 81% (high) to 50% (low). Individual counseling with CBT effectively helps students identify and change negative thought patterns that trigger social anxiety and improves adaptive social behavior.